Sonoelectrochemical and sonochemical effects of cavitation: correlation with interfacial cavitation induced by 20 kHz ultrasound. - Hardcastle, J; Ball, J; Hong, Q; Marken, F; Compton, R; Bull, S; Davies, S (Elsevier, 2000)
Sonoelectrochemical measurements at macro-electrodes under extreme conditions with a very short distance between ultrasonic horn tip and electrode and different ultrasound intensity levels are shown to result in violent cavitation detected in form of current peaks superimposed on the average limiting current. Analysis of the current data obtained for the oxidation of ferrocene in dimethylformamide (0.1 M NBu4PF6) at a 4 mm diameter Pt disc electrode and for the reduction of Ru(NH3)6(3+) in aqueous 0.1 M KCl at a 6 mm diameter Pt disc electrode consistently indicate a change of the physicochemical nature of sonoelectrochemical processes under extreme conditions. The sonoelectrochemical measurement of the rate constant for the carbon bromide bond cleavage of a 3-bromobenzophenone radical anion electrogenerated at a glassy carbon electrode in dimethylformamide solution in the presence of power ultrasound is shown to yield evidence for a breakdown of the conventional mass transport model of a planar diffusion layer under extreme conditions. The change can be correlated to the number of current data points deviating more than 10% from the mean of the current due to violent cavitation processes superimposed onto the average limiting current. Further, a study of the sonochemical destruction of aqueous dilute cyanide solution (in 0.1 M NaOH) demonstrates a correlation between the electrochemically detected cavitation violence and the sonochemical activity. Factors that govern the violence of interfacial cavitation appear to be directly proportional to the factors that make cavitation in the bulk solution chemically efficient.